Characteristic Profiles of Parasitic and Fungal Infections in Acute Diarrhea - Marcellus Simadibrata; Suzana Ndraha; Tjahjadi Robert Tedjasaputra; Ari Fahrial Syam; Achmad Fauzi; Murdani Abdullah; Abdul Aziz Rani (The Indonesian Society for Digestive Endoscopy, 2011)
Background: Diarrhea has been widely encountered in developing countries, including Indonesia. This study aimed to investigate the incidence of parasites and fungal infections, which also constitutes the etiologies of acute diarrhea. Method: A cross-sectional study was performed involving 93 patients. Patients with chief complaint of acute diarrhea were recruited at five hospitals in Jakarta, Indonesia during the period of November 2008 until May 2009. Acute diarrhea was defined as passing watery or soft stools with frequency of more than three times per day, weighted more 200 g per day, and occurred in less than 15 days duration. They were asked to collect their stool to the laboratory for further parasites and fungal detection. Results: This study showed that 41 out of 93 patients (44.09%) were found to be infected with parasites or fungi. The most common microorganism found was Candida albicans in 18 (19.35%) patients. Other parasites encountered in the stool samples were Blastocystis hominis, Entamoeba histolytica, Entamoeba coli, Giardia lamblia. The presenting clinical symptoms of the patients were fever (44.87%), bloating (41.03%), nausea (39.74%), oliguria (39.74%), cephalgia (35.90%), vomiting (24.36%), and tenesmus (19.23%). Conclusion: The incidence of parasitic and fungal infections in patients with acute diarrhea constitutes nearly half of all cases of infection-caused diarrhea. The most commonly encountered microorganism is Candida albicans. Keywords: parasites, fungi, acute diarrhea